Managing Moist Temperate Forests for Bioenergy and Biodiversity. Issue 1 (18th June 2015) - Root, Heather T.; Betts, Matthew G.
Abstract : Demand for bioenergy is expected to triple by 2050 as a result of policies aimed to improve energy independence and mitigate global climate change. We review forest practices that generate biomass in mesic forests and show that they vary widely in intensity and potential magnitude of the effects on biodiversity. Although increased demand for bioenergy may incentivize maintaining forestland, increasing economic value of woody biomass will probably stimulate more intensive management practices, impacting many species, especially those associated with deadwood. The spatial extent of habitat modification and the type and degree of management will have an impact on populations of sensitive species. We propose preliminary management guidelines to minimize biodiversity impacts and introduce an initial research agenda to test the sensitivity of forest biodiversity to bioenergy practices at multiple scales. Management and Policy Implications: Forest biomass use for energy is projected to increase due to policies promoting renewable energy sources. However, forest biomass harvesting strategies are highly diverse and have differing degrees of impact on forest biodiversity. Biomass harvesting is likely to result in increased utilization of forest elements previously considered to be "waste." For instance, greater rates of biomass extraction as a result of thinning or harvesting slash will cause reduced abundance of snags and coarse and fine wood in the future and potential declines in biodiversity associated with these features. In silvicultural systems designed primarily for biomass production (e.g., short-rotation woody crops and intensively managed plantations), there may also be greater effects on biodiversity associated with vertical and horizontal stand complexity. Although stand-level impacts may be estimated based on the habitat requirements of species, there has been little empirical research that tests for thresholds in the amount of bioenergy harvest above which native species are at risk; such vulnerability will be a function of both the area of land modified by bioenergy harvest and the intensity of management implemented. As the biomass-oriented harvests become increasingly common, it will be essential to examine both the stand- and landscape-level implications of these management practices on biodiversity.